(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The paper deals with the comparison of real estate price trends in two European markets such as Spain and Croatia, well-known tourist destinations. Trends in macroeconomic variables in the period from 2013 to 2022 were considered, such as the house price index, overdue mortgage or rent payments, direct investment, production in construction, real GDP per capita, average adjusted wage per employee and unemployment rate. The aim of this study is to compare real estate prices in these two countries with regard to macroeconomic variables. Methodology: The applied methodology is based on the model averaging technique, which has been used in a few previous similar research studies. Results: The obtained results point to the fact that real estate price movements are strongly negatively influenced by the unemployment rate in both observed countries. Conclusion: The real estate prices in Croatia are strongly negatively influenced by arrears on mortgage or rent payments, while in Spain, they are strongly positively influenced by production in construction. Recommendations for further research refer to research that would cover a wider range of Southeast European countries with common characteristics of strongly developed tourism.